Profiling Movement Quality Characteristics of Children (9-11y) During Recess - Cain Craig Truman Clark; Claire Marie Barnes; Huw D Summers; Kelly Mackintosh; Gareth Stratton (Asociación Española de Ciencias del Deporte, 2018)
Introduction. Frequency spectrum characteristics derived from raw accelerometry, such as spectral purity, have the potential to reveal detailed information about children's movement quality, but remain unexplored in children's physical activity. The aim of this study was to investigate and profile children's recess physical activity and movement quality using a novel analytical approach. Materials and Methods. A powered sample of twenty-four children (18 boys) (10.5±0.6y, 1.44±0.09m, 39.6±9.5kg, body mass index; 18.8±3.1 kg.m2) wore an ankle-mounted accelerometer during school recess, for one school-week. Hierarchical clustering, Spearman's rho and the Mann-Whitney U test were used to assess relationships between characteristics, and to assess inter-day differences. Results. There were no significant inter-day differences found for overall activity (P>0.05), yet significant differences were found for spectral purity derived movement quality (P<0.001). Overall activity was hierarchically clustered, and positively correlated, with spectral purity (P<0.05). Discussion. This is the first study to report spectral purity derived movement quality of children's physical activity in an uncontrolled setting and our results highlight potential for future research.